A review on application of enzymatic bioprocesses in animal wastewater and manure treatment. (October 2020) - Cheng, Dongle; Liu, Yi; Ngo, Huu Hao; Guo, Wenshan; Chang, Soon Woong; Nguyen, Dinh Duc; Zhang, Shicheng; Luo, Gang; Liu, Yiwen
Graphical abstract: Highlights: Enzymes pretreatment can improve the biodegradable of oily animal wastewater. Enzymatic prehydrolysis of fibers in animal manure enhanced biogas production. Enzymes type/source/dosage and operating conditions affect enzymatic bioprocesses. Abstract: Enzymatic processing has been considered an interesting technology as enzymes play important roles in the process of waste bioconversion, whilst heling to develop valuable products from animal wastes. In this paper, the application of enzymes in animal waste management were critically reviewed in short with respect to utilization in: (i) animal wastewater treatment and (ii) animal manure management. The results indicate that the application of enzymes could increase both chemical oxygen demand (COD) removal efficiency and production of biogas. The enzymatic bioprocesses were found to be affected by the type, source and dosage of enzymes and the operating conditions. Further studies on optimizing the operating conditions and developing cost-effective enzymes for the future large-scale application are therefore necessary.